Spatial Transcriptome Analysis Reveals Diverse Human Burn Wound Microenvironment. - Junak, Mary; Khatri, Parth; Zajac, Jocelyn; Kubica, Phillip; Yan, Di; Dinh, Huy Q.; Gibson, Angela L. F. (Wound Repair & Regeneration)
Histologic analyses of burn tissue are unable to discern reversible injury. Advanced molecular profiling, such as bulk RNA‐sequencing, provides more detail; however, these methods lose spatial context. Spatial transcriptomics allows gene transcripts to be mapped to tissue locations, revealing the molecular pathways activated in the burn tissue microenvironment, where the depth of injury guides prognosis. This work demonstrates the capability of spatial transcriptomics to detect spatial gene expression patterns in burn tissue. Specifically, we show that (i) spatially variable expressed genes are distinct across different burn depth regions, which would not be identified with bulk RNA‐sequencing, (ii) transcriptionally distinct burn tissue regions are defined by gene signatures associated with diverse cell types and biological pathways, and (iii) these spatial gene signatures are identified in a subset of previously published bulk samples, suggesting their potential application in large‐scale and integrated studies. Caveats of this technology in burn tissue are provided to guide future research. This study highlights the promise of spatial transcriptomics to understand the human burn wound microenvironment and identify specific regions with regenerative potential that can be the target of tailored therapeutics, providing an alternative to imprecise excision and skin grafting.